The World Tourism Organization Between Goals and Obstacles to Tourism Sustainability - Rouane, Lahcene; Drid, Kamel (Journal of Legal Studies and Researches, 2022)
In this research paper, we aim to define the Organization's objectives in the context of sustainable development in its various dimensions in support of the global tourism sector, as well as to highlight some of the challenges it faces, we found that the organization works to achieve tourism sustainability and contribute to quality of life, but the tourism is highly vulnerable to the most recent of which is Covid-19